Graphene: A Versatile Carbon-Based Material for Bone Tissue Engineering - Nileshkumar Dubey; Ricardo Bentini; Intekhab Islam; Tong Cao; Antonio Helio Castro Neto; Vinicius Rosa (Hindawi Limited, 2015)
The development of materials and strategies that can influence stem cell attachment, proliferation, and differentiation towards osteoblasts is of high interest to promote faster healing and reconstructions of large bone defects. Graphene and its derivatives (graphene oxide and reduced graphene oxide) have received increasing attention for biomedical applications as they present remarkable properties such as high surface area, high mechanical strength, and ease of functionalization. These biocompatible carbon-based materials can induce and sustain stem cell growth and differentiation into various lineages. Furthermore, graphene has the ability to promote and enhance osteogenic differentiation making it an interesting material for bone regeneration research. This paper will review the important advances in the ability of graphene and its related forms to induce stem cells differentiation into osteogenic lineages.